The Impact of Medical Graduate Students’ Research Burnout on Team Performance: A Mediated Moderation Model - Cai, Danli (Journal of Educational Research and Policies, 2026)
Objective: To explore the influencing mechanism and the mechanism of action of research burnout among medical graduate students and their team performance. Methods: From August 2025 to November 2025, a questionnaire survey was conducted on 472 medical graduate students from three medical universities in Zhejiang Province (Zhejiang University, Wenzhou Medical University, and Hangzhou Medical College) using the Mentor Support Scale, Research Burnout Scale, Psychological Empowerment Scale, and Team Performance Scale. Results: (1) Research burnout has a negative impact on predicting the team performance of medical graduate students (r = -0.367, P < 0.001); (2) Psychological empowerment has a significant mediating effect between research burnout and team performance (β = -0.209, t = -4.739, P < 0.001); (3) The relationship between research burnout and psychological empowerment (i.e., the first half of the mediating effect path) is regulated by mentor support (β = 0.123, t = 3.421, P < 0.01). Conclusion: Research burnout can directly predict team performance, and it can also affect team performance through the mediating effect of psychological empowerment, and the mediating effect is regulated by mentor support.